Odpowiedzi

2009-12-09T18:14:01+01:00
A) (x+1)(x-2)+(x+2)(x-1) =2x-x+2x=3x

b) (5k+n)(k-2n)-k(4k+n) =(5k+n)(k-2n)-k(4k-n)=5k-2n

c) (4y+3)(y-2)-2y(4-2y) =(4y+3)(y-2)-2y(4+2y)=4y+y-2y+2y+3+4=4y+7
d) -(3c-2)(c-1)-c(c-2) =3c+2(c-1)-c(c+2)=3c+2c-2+2=5c
e) 2(3a²-1)-(a+2)(a+2) =6a²-2-a-2(a+2)=6a²-2-a-2a+4=6a²-a-2a-2+4=4a+2
f) 5x²(x²+1)-(x²+1)(x²+3) = 6x²+5x²-x²-1(x²+3)=8x²+3
Najlepsza Odpowiedź!
2009-12-09T18:36:53+01:00
A)(x+1)(x-2)+(x+2)(x-1)=x²-2x+x-2+x²=2x²-2
b) =5k²-10kn+kn-2n²4k²-kn=k²-2n²-10kn
c =4y²-8y+3-6-8y+4y²=16y²-16y+3
d =[-3c+2][c-1]-c²+2c=-3c²+3c+2c-2-c²+2c=-4c²+7c-2
e =6a²-2-a²-2a-2a-4=5a²-4a-6
f =5x⁴+5x²-[x⁴+3x²+x²+3]=5x⁴+5x²-x⁴-3x²-x²-3=4x⁴+x²-3
1 1 1